Gender diversity and ownership structure of Malaysian firms in the real estate sector - Amran, Noor Afza; Abdullah, Zaimah; Ishak, Rokiah (Academic Research Publishing Group, 2018)
This study aims to examine the relationship between gender diversity and real estate companies’ performance in Malaysia, whereby in 1985, the Government of Malaysia formulated a National Policy on Women as a guide for women’s participation. Panel data analysis was used to examine the gender diversity and real estates’ performance in an unbalanced panel of 549 observations for the years 2012-2015. The authors utilised an agency theory to inform the discussion of this paper’s findings. This study finds that the woman directors in the real estate companies are dominated by family-companies. The existence of block holders enhances the firm governance by monitoring the board activities which in turn increase their effectiveness and efficiency that lead to a higher firm performance. Both the managerial ownership and the institutional investors are significant in determining the firm’s performance. The reason may be due to higher ownership controlled by managerial and investor which makes them have a say in a company and try to pursue their objectives rather than the stakeholders’ interests. The findings have contributed to the body of knowledge especially on the women participation in Malaysia, and their contributions. Gender diversity does not destroy the firm performance; in fact, Malaysian companies should focus on the right combination of men and women on the board, rather than the presence of at least a woman on a board of directors. The findings outlay the scenario of women’s involvement in the real estate companies in Malaysia. There is a positive direction for women’s involvement in the board, but it is still a long way to go. Very limited studies delved on gender diversity and real estate companies in Malaysia, even though there is a policy by the Government on women involvement in Malaysia.